BILINGUISMO ADITIVO: UM ESTUDO DE CASO DE PARENTALIDADE BILÍNGUE EM SEGUNDA LÍNGUA EM UMA FAMÍLIA DE CURITIBA – PR - BATISTA, ANALINE BADOTTI (2021)
This research is about additive bilingualism, more specifically about a case of non-native bilingual parenting in a family in Curitiba – PR. The general objective was to analyze the family linguistic policy of a Brazilian family from the introduction of the “OPOL” methodology as a strategy for introducing Portuguese-English additive bilingualism. Therefore, the theoretical foundation, in the field of Psychology theory, is essentially based on: King (2006), Sauders (1988), Baker (1995), King, Logan-Terry (2008), Houwer (2011) and Döpke (1998). The research methodology is qualitative in nature and consists of a “case study” in which the father, 51 years old (subject 1) and the daughter, 13 years old (subject 2), were periodically interviewed through a semi structured questionnaire. The results reveal that, in addition to being possible to develop a second language in the family environment, it is noted the relevance of considering the narratives presented by the subjects, as well as their historical-social conditions that constitute them. From this, it intends to contribute to the dissemination of scientific knowledge about the OPOL methodology in families who wish to provide second language learning in the family environment.